Problematika pembelajaran bahasa arab bagi siswa lulusan SMP di pondok pesantren darunnajah : Problematika pembelajaran bahasa arab bagi siswa lulusan SMP di pondok pesantren darunnajah - ratika permata sari (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
Learning Arabic is one of the main pillars pf Education at Islamic boarding school. However, junior high school graduate students often face various difficulties in participating in this Learning, especially at the Darun Najah Islamic boarding school. Thus Research examines the factors that influence the effectiveness of Arabic language Learning, both in terus of internal students such as motivation, basic abilities, and learning readiness, as well as from external aspects such as curiculum, teaching methods, and learning environment, the research was carried out using A qualitative approach through observation, in-depth interviews and dokumentasi analysis. The results show that students have difficulity mastering aspects of grammar (nahwu and sharaf), vocabulary, and speaking skill. The research provides a number of strategic recommendations, including curiculum revisi, teaching methods Innovation, and improving the learning en